Kinetic field theory: effects of modified gravity theories with screening mechanisms on non-linear cosmic density fluctuations - Oestreicher, Alexander; Saxena, H.; Reinhardt, Niklas; Kozlikin, Elena; Dombrowski, J.; Bartelmann, Matthias (Journal of cosmology and astroparticle physics, 2025)
In a mean-field approximation within Kinetic Field Theory, it is possible to derive an accurate analytic expression for the power spectrum of present-day non-linear cosmic density fluctuations. It depends on the theory of gravity and the cosmological model via the expansion function of the background space-time, the growth factor derived from it, and the gravitational coupling strength, which may deviate from Newton's constant in a manner depending on time and spatial scale. In earlier work [1], we introduced a functional Taylor expansion around general relativity and the cosmological standard model to derive the effects of a wide class of modified-gravity theories on the non-linear power spectrum, assuming that such effects need to be small given the general success of the standard model. Here, we extend this class towards theories with small-scale screening, modeling screening effects by a suitably flexible interpolating function. We compare the Taylor expansion with full mean-field solutions and find good agreement where expected. We find typical relative enhancements of the non-linear power spectrum between a few and a few ten per cent in a broad range of wave numbers between k ≳ 0.1-10 h Mpc, in good qualitative agreement with results of numerical simulations. Taking nDGP gravity as a quantitative example we compare our results to N-body simulations and find percent-level agreement for wavenumbers k ≲ 2 h Mpc-1, if the scale where screening sets in, k *, is adapted appropriately. This extends the application of our analytic approach to non-linear cosmic structure formation to essentially all classes of modified-gravity theories.